Study design and methods for the physical activity index (PAI) feasibility pilot trial for breast and colon cancer survivors in North Carolina - Bluethmann, Shirley M.; Tooze, Janet; Evans, Joni K.; Katula, Jeffrey; Wood, Kristy; Hitariansingh, Lesley; Crotts, Charlotte; Klepin, Heidi D.; Paluri, Ravi; Kadakia, Kunal; Ansley, Katherine (Contemporary clinical trials communications, 2025)
The majority of the 18 million US adults with cancer history (“survivors”) do not meet recommendations for obtaining regular physical activity (PA) or limiting sedentary behavior in their daily lives. Breast cancer survivors (BCS) and colon cancer survivors (CCS) are particularly at risk of insufficient PA and excessive sedentary behavior (i.e., sitting) that may increase physical impairments, worsen cancer treatment symptoms, limit optimal cancer recovery, and limit opportunities to potentially reduce cancer risk. Research has shown that completion of clinical cancer treatment may serve as a ‘teachable moment’ for patients as they transition to recovery at home. Many of these survivors are uncertain about building a healthier lifestyle without guidance from the medical team, but few validated clinical tools exist to assess and counsel survivors on their behavioral choices relative to PA and sedentary behavior. Based on our recent findings, a simple screener that collects measures on PA, strength training, and sedentary behavior, the Physical Activity Index (PAI), may be effective for clinical use to monitor patient behaviors and provide specific, tailored recommendations on how to achieve and maintain behavioral goals. We propose a multicomponent, two-arm pilot 1:1 randomized controlled trial with waitlist control in which we will recruit (n = 20) BCS and CCS within three years of diagnosis to leverage the ‘teachable moment’ in early recovery. The PAI intervention will include standard survivorship follow-up care plus a PA assessment using the PAI screener that is supplied to the provider plus five remote coaching consultations with a certified exercise physiologist. All participants will also receive resistance bands to keep and an activity tracker to self-monitor their behaviors at home. We will determine feasibility by examining recruitment, retention, acceptability, and PAI intervention adherence goals. Secondarily, we will measure changes/variability in achievement of behavioral outcomes for PA and sedentary behaviors to inform future trial planning.